Dynamics of Stakeholder Collaboration in Bojonegoro's Open Data Program - Nafi’ah, Binti Azizatun (Indonesian Association for Public Administration, 2020)
This paper discusses the complexity of collaboration dynamics and the open data of collaboration cycle in Bojonegoro Regency. Bojonegoro's open data is a data development program that is collected from the PKK Dasawisma data updated once a month through the publication of Dasawisma data online. This paper has proven a very dynamic level of collaboration in open data initiation through the use of qualitative techniques by collecting data on interviews, observations, and documentation. The level of collaboration dynamics is promoted by drivers in the form of leadership, a culture of openness that has been formed, resource dependence on one another and strong local CSO roles. These drivers are determinants dynamics of open data collaboration to reach a mature collaboration cycle. Some findings indicating weaknesses are the